Contemplative Hermeneutics on John’s Epistemology Applied in the Public Square in the Context of Romanian Pentecostalism - Pop, Andrei-Daniel (Bogoslovskie razmyšlenija, 2019)
Starting from the reality of Romanian evangelical churches where most of the sermons and Bible messages are directive, which reflect a hermeneutic of the same type (only directives, indications and recommendations are usually presented), we can see that it is necessary to elaborate a comparative study in the domain of practical and public theology, which will show the clear superiority of contemplative hermeneutics which is concentrated on God’s person. In other words, I propose a demonstration of the fact that a contemplative hermeneutics is more efficient than a directive hermeneutics for Romanian Pentecostalism and for the way the message of the Gospel is addressed in the public square. Our love in action can be seen in the public square by our proclamation, and for a proper proclamation we need a proper hermeneutic, and in my opinion this one is the contemplative hermeneutic. The reason for choosing John’s epistemology through the statements "I am" to prove the superiority of contemplative hermeneutics, is the fact that John`s perspective offers a complex contemplative (epistemological) picture of the person of Jesus Christ. In the final part of my writing I want to demonstrate that the application of contemplative hermeneutics is actually a homiletics in the same way, and in this homiletics Christ is the center of the message, and not a collection of rules and interdictions reflected by a directive hermeneutics. I consider that through this approach the message of the Church in the Public Square is full of substantial content, which can make a difference in the context of a secularized society on the one hand, and on the other hand a society characterized by the post-modern thinking, in which experience is --very important, and contemplative hermeneutics offers the chance to experience the power of the Gospel in the public square and also at an individual level.